Water and Society: Contextualization of Science in Politics and Public Policy - Cahyo Seftyono; Andy Bangkit Setiawan; Erisandi Arditama (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2017)
A study of science today is inseparable from a diversity of contexts. This is also reflected in society’s discourse on the positioning of science itself. To that end, principles of science cannot be actualized as such, rather must be underpinned by society needs that are reflected in research and pre requisites of science manifested in reengineered forms. Findings that relate to the environment, especially water, are crucial today in many areas.   By using a comparative and in-depth interview methodologies in a qualitative manner, this article which is based on a research that was conducted during   2008-2016 period in Code- Yogyakarta city (Indonesia), Air Panas Diwak- Semarang (Indonesia), Umbul Cokro-Klaten (Indonesia), Rawa Pening-Salatiga district (Indonesia), Curug Kalisidi- Semarang city (Indonesia) and Tasik Chini- Negeri Pahang (Malaysia), makes it interesting for a variety of reasons. First, based on a lot of previous literature, this article makes an argument that water with all its manifestations and forms, must have the quality of fulfilling needs of society. Water as an integral part of science, is accorded the position of a subject as well as an object in relation to society.